On the Oscillation of Even-Order Half-Linear Functional Difference Equations with Damping Term - Bolat, Yaşar; Alzabut, Jehad (Wiley, 2014)
We investigate the oscillatory behavior of solutions of themth order half-linear functional difference equations with damping term of the formΔ[pnQ(Δm-1yn)]+qnQ(Δm-1yn)+rnQ(yτn)=0,n≥n0, wheremis even andQ(s)=sα-2s,α>1is a fixed real number. Our main results are obtained via employing the generalized Riccati transformation. We provide two examples to illustrate the effectiveness of the proposed results.
Keywords: Oscillation theory for difference equations; QA1-939; Discrete version of topics in analysis; Mathematics; Additive difference equations; 16. Peace & justice